2000
DOI: 10.1086/316902
|View full text |Cite
|
Sign up to set email alerts
|

Two Loci on Chromosomes 2 and X for Premature Coronary Heart Disease Identified in Early- and Late-Settlement Populations of Finland

Abstract: Coronary heart disease (CHD) is a complex disorder constituting a major health problem in Western societies. To assess the genetic background of CHD, we performed a genomewide linkage scan in two study samples from the genetically isolated population of Finland. An initial study sample consisted of family material from the northeastern part of Finland, settled by a small number of founders approximately 300 years ago. A second study sample originated from the southwestern region of Finland, settled approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 51 publications
5
86
2
Order By: Relevance
“…However, both of these scenarios would have less impact on public health issues or the development of new treatment strategies, although particularly a rare polymorphism with a strong effect could be of great importance to the individual. Our findings are also supported by the results of the genome-wide screens that have been published in the field of premature coronary artery disease (Pajukanta et al 2000, Francke et al 2001, Broeckel et al 2000, Harrap et al 2002. In none of these studies have potentially important LOD scores (>1) been reported for these regions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, both of these scenarios would have less impact on public health issues or the development of new treatment strategies, although particularly a rare polymorphism with a strong effect could be of great importance to the individual. Our findings are also supported by the results of the genome-wide screens that have been published in the field of premature coronary artery disease (Pajukanta et al 2000, Francke et al 2001, Broeckel et al 2000, Harrap et al 2002. In none of these studies have potentially important LOD scores (>1) been reported for these regions.…”
Section: Discussionsupporting
confidence: 85%
“…However, it is important to note that the number of affected sibling pairs recruited into our study was larger than that of all four recently published genome-wide screens (Pajukanta et al 2000, Francke et al 2001, Broeckel et al 2000, Harrap et al 2002. Compared to genome-wide screens, our study will also have superior power to exclude linkage to the relevant loci because the recombination fraction approaches zero in our design (Risch 1990a, John et al 1997.…”
Section: Discussionmentioning
confidence: 97%
“…Case-control association studies have identified several proinflammatory genes with variants that are associated with either an increased risk of myocardial infarction or a protective effect [7][8][9] . Four genome-wide scans in families with myocardial infarction have yielded several loci with formidable linkage peaks, but the gene(s) underlying these loci have not yet been identified [10][11][12][13][14] . In addition, one large pedigree study identified a deletion mutation of a transcription factor gene, MEF2A, with autosomal dominant transmission 14 .…”
mentioning
confidence: 99%
“…Although CAD can also rarely be inherited in a Mendelian fashion (predominantly in conditions leading to elevated LDL), this only accounts for a small proportion of incident cases [7], most of which are likely to be polygenic. Linkage studies of non-Mendelian CAD have provided some unbiased associations [8][9][10][11][12][13][14][15][16], even though these have conspicuously lacked reproducibility between cohorts. However, linkage studies will always suffer from poor statistical power and the lack of detailed genomic mapping provided by conventional microsatellite markers.…”
Section: Genome-wide Association Studies: Getting Closer To the Genetmentioning
confidence: 99%